Von Economo Neurons – Primate-Specific or Commonplace in the Mammalian Brain? - Banovac, Ivan; Sedmak, Dora; Judaš, Miloš; Petanjek, Zdravko (Frontiers in Neural Circuits, 2021)
The pioneering work by von Economo in 1925 on the cytoarchitectonics of the cerebral cortex revealed a specialized and unique cell type in the adult human fronto-insular (FI) and anterior cingulate cortex (ACC). In modern studies, these neurons are termed von Economo neurons (VENs). In his work, von Economo described them as stick, rod or corkscrew cells because of their extremely elongated and relatively thin cell body clearly distinguishable from common oval or spindle-shaped infragranular principal neurons. Before von Economo, in 1899 Cajal depicted the unique somato-dendritic morphology of such cells with extremely elongated soma in the FI. However, although VENs are increasingly investigated, Cajal’s observation is still mainly being neglected. On Golgi staining in humans, VENs have a thick and long basal trunk with horizontally oriented terminal branching (basilar skirt) from where the axon arose. They are clearly distinguishable from a spectrum of modified pyramidal neurons found in infragranular layers, including oval or spindle-shaped principal neurons. Spindle-shaped cells with highly elongated cell body were also observed in the ACC of great apes, but despite similarities in soma shape, their dendritic and axonal morphology has still not been described in sufficient detail. Studies identifying VENs in non-human species are predominantly done on Nissl or anti-NeuN staining. In most of these studies, the dendritic and axonal morphology of the analyzed cells was not demonstrated and many of the cells found on Nissl or anti-NeuN staining had a cell body shape characteristic for common oval or spindle-shaped cells. Here we present an extensive literature overview on VENs, which demonstrates that human VENs are specialized elongated principal cells with unique somato-dendritic morphology found abundantly in the FI and ACC of the human brain. More research is needed to properly evaluate the presence of such specialized cells in other primates and non-primate species.